Improvement of the extruder body design in order to increase reliability and quality of extrusion - Kazak, Iryna (Technology audit and production reserves, 2021)
The article highlights one of the ways to improve the design of the extruder body in order to increase the reliability and, at the same time, the quality of extrusion. The object of research is a single-worm extruder. One of the most problematic areas of the extruder is the body. The main disadvantage of the extruder is the wear of the body surfaces due to corrosion or abrasion and requires regular replacement. This is due to the abrasive properties of the polymers and, accordingly, due to the friction of the polymer material against the body and the worm, especially due to contamination in the recycled material. In various sources, the replacement of the extruder worm with a more advanced design is widely covered. And scientists do not pay enough attention to improving the body of the extruder, which indicates the relevance of this study. That is why the problem of increasing the reliability of the extruder body is completely unsolved and urgent. In the course of the study, we used an analysis of the structural features of the extruder body, a literature-patent review of existing methods for improving the body of a single-worm extruder to increase the reliability and, at the same time, the quality of extrusion. As a result of the literature and patent review, the option of improving the extruder body based on the prototype of the split body, which additionally contains an inner surface of steel ribbed plates, was selected. It was found that the ribbing of the plates on the inner surface of the body increases the wear resistance of the body and promotes more intensive advancement of the polymer used material to the extruder head. This is due to the fact that the proposed improved body of the extruder has a number of features: steel ribbed plates rigidly fixed inside it are installed with overlap of the parting line of the extruder body. This makes it possible to increase the wear resistance and, accordingly, the reliability of the extruder body and, additionally, the extrusion quality. Compared with the known one-piece structures of the extruder body, the design of the body is detachable with steel rigidly mounted ribbed plates on the inner surface, which will simplify maintenance during repairs and, at the same time, improve the quality of extrusion.